2023
DOI: 10.1088/1361-6668/ace65f
|View full text |Cite
|
Sign up to set email alerts
|

High-energy electron local injection in top-gated metallic superconductor switch

Abstract: The gate-tunable superconductivity in metallic superconductors has recently attracted significant attention due to its rich physics and potential applications in next-generation superconducting electronics. Although the operating principles of these devices have been attributed to the small leakage currents of high-energy electrons in recent experiments, the generated phonons can spread over considerable distances in the substrate, which may limit their further applications. Here, we utilize a top gate structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We note that there is only one report to date about the observation of a GCS in micrometer-wide Nb bridges (i.e., with w S ≫ ξ), but these devices have a top-gate other than a side-gate geometry, unlike the ones investigate in the present study. In a device with a top gate, the most relevant dimension for the GCS is not w S but the S thickness, which in ref is ∼6 nm and hence still comparable to ξ (<15 nm; ref ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We note that there is only one report to date about the observation of a GCS in micrometer-wide Nb bridges (i.e., with w S ≫ ξ), but these devices have a top-gate other than a side-gate geometry, unlike the ones investigate in the present study. In a device with a top gate, the most relevant dimension for the GCS is not w S but the S thickness, which in ref is ∼6 nm and hence still comparable to ξ (<15 nm; ref ).…”
Section: Resultsmentioning
confidence: 98%
“…The control of a superconducting current (supercurrent) via the application of a gate voltage ( V G ), currently known as gate-controlled supercurrent (GCS), has become a subject of great interest, as evidenced by the number of experimental and theoretical studies reported on it. Among the main motivations behind the interest in the GCS is its potential for the development of voltage-controlled superconducting logics that would intrinsically have low-energy dissipation (since based on superconductors) and better performance than other superconducting logics already available. Compared to these, GCS-based logics would offer several advantages including higher device density (due to the smaller device size), larger number of devices connectable in series (i.e., higher fan out), stronger resilience to magnetic noise and easier interfacing with conventional metal-oxide semiconductor (CMOS) circuits to form hybrid superconducting/semiconducting computing architectures .…”
mentioning
confidence: 99%
See 1 more Smart Citation